Performance Analysis of TCP Tahoe, Reno and New Reno for Scalable IoT Network Clusters in QualNet® Network Simulator - Mishra, Ayaskanta (International Journal of Computer Sciences and Engineering, 2018)
In the era of Internet of Things, sensors and actuators equipped embedded devices are seamlessly connected over internet using TCP/IP stack to enable various M2M applications and services for users. Transmission Control Protocol (TCP) is a connection oriented protocol in Transport layer of OSI providing guaranteed service for various Internet of things (IoT) applications like HTTP, MQTT and CoAP (over TCP RFC 8323). Further, Congestion Avoidance and Control mechanism implemented in TCP makes it more adaptive to various network conditions. It is imperative to design an IoT network cluster aided with a reliable transport layer TCP for sending sensor data to a cloud server or to control actuators using HTTP Representational state transfer (REST) APIs. In this paper, three network performance matrices namely Throughput, End-toEnd delay and Packet deliver ratio (PDR) are considered to evaluate the performance of TCP Tahoe, Reno and New-Reno in multiple network clusters designed for IoT applications. QualNet® 6.1 network simulator is used to simulate scalable wired (IEEE 802.3 Ethernet) and wireless (IEEE 802.11 Wireless LAN) IoT network clusters. From the perspective of this paper, multiple test cases of IoT network clusters are considered to analyze the performance of TCP variants with a scalable approach by varying node density and by varying Maximum Segment Size (MSS).